Pengaruh Penggunaan Model Pembelajaran Two Stay Two Stray Berbatu Media Dokar Saja Terhadap Hasil Belajar Aksara Jawa Siswa Kelas IV - Andriyanti, Siti Dwi; Purwati, Purwati; Istiningsih, Galih (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of using the twostay twostray learning model with the help of gig media on learning outcomes of Javanese script in fourth grade students of Gondangrejo State Elementary School, Windusari, Magelang. The design of this study used a Pre-experimental design with the One Group Pretest Posttest Design research model. This research was conducted on fourth grade students of Gondangrejo State Elementary School Windusari Magelang. The research sample was taken in total from the population with a sample of 20 students using a total sampling technique. The method used in collecting data in this study used the test method. The validity test carried out in this study is construct validity and empirical validity. The reliability test uses Cronbach's alpha which produces a reliability index of 0.837. Prerequisite test consists of normality test and homogeneity test. The normality test in this study obtained a significance value of 0.25 > 0.05 where the data was declared normal. Hypothesis testing using parametric statistical techniques, namely the Paired sample t test, The results of the hypothesis test are shown by the paired sample t test of Javanese script learning outcomes with a value of7. 725> 0.05, which indicates that there is an effect of using the Two Stay' Two Stray Learning Model with the help of Dokar Media Only on Javanese Script Learning Outcomes. The results of this study prove that there is an effect of using the Two Stay' Two Stray' Learning Model with the help of Dokar Media Only' on the Learning Outcomes of Javanese Script,